Simulating forest dynamics of a tropical montane forest in South Ecuador - Dislich, Claudia; Günter, Sven; Homeier, Jürgen; Schröder, Boris; Huth, Andreas (ERDKUNDE, 2009)
The montane forests of Ecuador are part of one of the world’s hotspots of biodiversity and they also suffer the highest deforestation rate amongst South American countries. The processes that drive the dynamics of these highly diverse ecosystems are poorly understood. This is particularly true for transient dynamics, which are crucial for the protection and sustainable management of such forests. Dynamic simulation models can be used to analyse the growth of forests, but so far they have been applied mostly to temperate forests and to some few tropical lowland forests. In this study we investigate whether a process-based, individual-oriented simulation model like FORMIND is capable of reproducing the dynamics of tropical montane forests. For this purpose we develop a parameterisation for the model and validate the model against field observations of different (structural) patterns. We then analyse the predicted succession dynamics. The model is capable of reproducing the structure and dynamics of mature ridge forest on different levels of complexity. The main results indicate that, in terms of relative abundances of different species groups and stem size distribution in the tree community, our model predicts the observed patterns in the field. Additional field studies and model modifications are required to simulate the succession processes that follow different types of disturbances. FORMIND is a promising tool for the extrapolation of local measurements and for simulating the dynamics of tropical montane forests. Parameterisations of the model for further forest types within the research area are intended. The model has a number of potential applications, ranging from investigating the impact of (different) natural disturbances on forest structure and tree species diversity to analysing different potential management strategies.